IMPLEMENTASI MODEL PEMBELAJARANPROJECT BASED LEARNING DALAM MENGEMBANGKAN KREATIVITAS BELAJAR SISWA MATAPELAJARAN PAI KELAS VIII SMP NEGERI 7 SAMBAS - Aidil Fitri; Mujahidin; Firli Ariska (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study aims to describe the implementation of the Project Based Learning (PjBL) model in developing students’ learning creativity in Islamic Religious Education (PAI) for eighth-grade students at SMP Negeri 7 Sambas. The study examines how PjBL stimulates students’ learning creativity, the supporting and inhibiting factors in its implementation, and its impact on students’ learning attitudes. This research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results indicate that the implementation of PjBL is able to increase students’ activeness, creativity, and independence in the learning process. Supporting factors include the availability of learning media, teacher support, and collaboration among students, while inhibiting factors consist of limited time and students’ lack of experience in project-based learning. Furthermore, PjBL has a positive impact on students’ learning attitudes, as reflected in increased responsibility, collaboration skills, as well as learning interest and motivation.